What works in rural advisory services? - Davis, Kristin E.; Bohn, A.; Franzel, Steven; Blum, Magdalena L.; Rieckmann, U.; Saravanan, Raj; Hussein, K.; Ernst, Natalie (Global Forum for Rural Advisory Services, 2018)
The notes also explain the different ways in which an approach has been used, and how it has been adapted to different contexts and countries. In addition to extension managers and practitioners, other audiences who will find the notes useful include staff and students in universities and other educational institutions, researchers, policy-makers, producer organisations and private companies buying produce from farmers, and development practitioners interested in promoting agricultural innovations.